Vibration analysis of hand tools used in manufacturing industry [electronic resource] - 237465 Shahrol Faizal Wahab (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2008